OCORRÃŠNCIA DE Psyllaephagus bliteus RIEK (HYMENOPTERA: ENCYRTIDAE) NO BRASIL - Berti Filho, Evoneo; Costa, Valmir Antonio; Zuparko, Robert L.; LaSalle, John (REVISTA DE AGRICULTURA, 2015)
OCORRÃŠNCIA DE Psyllaephagus bliteus RIEK (HYMENOPTERA: ENCYRTIDAE) NO BRASIL